2018
DOI: 10.1155/2018/8483401
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Operation in the Treatment of Boerhaave’s Syndrome

Abstract: Purpose This study aims to discuss the appropriate treatment strategy for spontaneous esophageal rupture. Methods Clinical data from twenty-one cases were retrospectively analyzed. The parameters included etiology, time interval between onset and treatment, therapy methods, prognosis, and length of stay. Results The ratio of males/females was 17/4, age range was 32–82 years (mean = 43.1), and the time interval between onset and treatment was as follows: <24 h: nine cases (42.8%); 24–48 h: six cases (28.6%); an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 19 publications
1
38
1
1
Order By: Relevance
“…BS, to our knowledge, has been demonstrated in various patients, including those with gastrointestinal stenosis, Barrett's oesophagus, ileus, and frequent vomiting during continued chemotherapy or gastroscopy and after general anaesthesia [3]. However, in our case, the patient's esophageal wall tear was unusually secondary to oral magnesium sulfate administration, and second, most unique to our case, his rupture was located in the right wall of the distal oesophagus, which was in disagreement with the most frequent site of perforation reported [5]. To our knowledge, this is the rst published case worldwide demonstrating esophageal rupture located in the right wall after taking magnesium sulfate.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…BS, to our knowledge, has been demonstrated in various patients, including those with gastrointestinal stenosis, Barrett's oesophagus, ileus, and frequent vomiting during continued chemotherapy or gastroscopy and after general anaesthesia [3]. However, in our case, the patient's esophageal wall tear was unusually secondary to oral magnesium sulfate administration, and second, most unique to our case, his rupture was located in the right wall of the distal oesophagus, which was in disagreement with the most frequent site of perforation reported [5]. To our knowledge, this is the rst published case worldwide demonstrating esophageal rupture located in the right wall after taking magnesium sulfate.…”
Section: Discussioncontrasting
confidence: 77%
“…Spontaneous oesophageal rupture, also known as Boerhaave syndrome (BS), is a life-threatening benign disease of the gastrointestinal tract [3] that typically results from a sudden increase in intraoesophageal pressure such as forceful retching or severe vomiting [4] and most frequently occurs in the left wall of the lower third of the oesophagus, a site that is anatomically vulnerable [5]. BS, to our knowledge, has been demonstrated in various patients, including those with gastrointestinal stenosis, Barrett's oesophagus, ileus, and frequent vomiting during continued chemotherapy or gastroscopy and after general anaesthesia [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is as of yet no de nitive treatment approach, according to current retrospective analysis and clinical experiences, application of operative intervention to repair breakage primarily is considered as priority in current management of Boerhaave's syndrome, especially in the condition as we reported that the patient had presented signs of contamination of the pleural cavity and mediastinum [6].…”
Section: Discussionmentioning
confidence: 97%
“…Currently, BS and more generally esophageal perforations are considered as catastrophic conditions, often life-threatening, with 10 to 40% mortality rates (even higher rates are reported in septic patients with spontaneous perforations) [2]. Due to its very low incidence and aspecific features, more than 50% of cases are misdiagnosed, with a subsequent delay in treatment [3,4].…”
Section: Introductionmentioning
confidence: 99%